(untitled) (World Bulletin of Social Sciences, 2021)
Today, a lot of attention is paid to education. In particular, the issues of improving the quality of education and training of qualified personnel are rising at the state level. These issues are especially important in preschool and secondary education. In this article, the author details the importance of the assessment system in secondary schools in the international context.